Pengaruh Kualitas Pelayanan Terhadap Kepuasan Tamu di Hotel Horison Bandar Lampung - Pramudito; Faiza Rachim; Mochamad Achmadi; Linda Desafitri Ratu Bilqis; Braja Eka Sukma (Journal of Hospitality Accommodation Management (JHAM), 2025)
This study aims to analyze the effect of service quality, consisting of five SERVQUAL dimensions, on guest satisfaction at Horison Hotel Bandar Lampung. A quantitative approach with multiple linear regression analysis was employed in this study. Data were collected through questionnaires distributed to 100 respondents staying at the hotel and were analyzed using validity tests, reliability tests, coefficient of determination tests, partial tests, and simultaneous tests. The results showed that all five dimensions of service quality had a significant effect on guest satisfaction. The tangibles dimension had an impact due to the comfortable and modern physical appearance of the hotel, reliability due to service consistency, responsiveness related to the speed and accuracy of staff responses, assurance related to guests’ sense of security and trust in staff, and empathy reflected in personal attention to guests. Based on these findings, it is recommended that hotel management continue to improve service quality by paying attention to these five dimensions to enhance guest satisfaction and loyalty. Guests are also encouraged to provide constructive feedback so that the hotel can continuously improve its service quality.